Quantity And Quality Of DNA Extracted From Blood Stains On The Blade After Exposure To Ultraviolet Light And The Sun - Prasetyoningrum, Putri Arie; Junitha, I Ketut; Yulihastuti, Dwi Ariani (Metamorfosa: Journal of Biological Sciences, 2023)
Examination of Deoxyribonucleic Acid is the primary identification method in forensic cases. Blood stains found at the scene of a crime are often affected by various environmental factors, one of which is ultraviolet light from the sun. Purpose of this study is to compare the quantity and quality of DNA extracted from blood stains on the blade after exposure to ultraviolet light and the sun for 0, 15 and 30 days. The method used is a factorial design: light source (UVA, indirect sunlight and direct sunlight); and duration of treatment (0, 15 and 30 days). Blood stains are made by dripping a 50?L of human blood on one side of the blade and then given treatment. DNA analysis includes: extraction with Chelex 5%; DNA quantity and quality test with SimpliNano spectrophotometer; total DNA quality test with agarose gel electrophoresis; and PCR. Quantitative data analysis using Univariate test followed by Duncan test. The results showed that the quantity of DNA in samples exposed to UVA and sunlight (directly) increased on the 15th day due to DNA fragmentation while samples exposed to sunlight (indirectly) decreased the quantity of DNA with the duration of treatment. DNA quality in the form of DNA purity produces an extract of DNA that is not pure. The total DNA quality with agarose gel electrophoresis on all samples showed that the longer the treatment (0, 15 and 30 days) resulted in a dimmer or thinner band of DNA luminescence with smears.